Nurturing waqf-based social entrepreneurs in higher learning institutions in Malaysia / Nurjannah Salleh, Abd Halim Mohd Noor and Roshayani Arshad - Salleh, Nurjannah; Mohd Noor, Abd Halim; Arshad, Roshayani (Center for Islamic Philantrophy & Social Finance (CIPSF), 2020)
Waqf-based entrepreneurship among higher education students has been recognised as a chance to provide benefits to the students in terms of self-employment, creating job opportunities and reducing unemployment among graduates. The literature has adopted different to better understand waqf-based entrepreneurship. However, practitioners and researchers have only focused on conceptual approaches. Even though this literature forms part of the solution in this area of study, it does not represent the problem holistically. Waqf-based entrepreneurship requires an understanding on the functions of waqf as the Islamic endowment. It's provides a structure for understanding the social contexts that have high potential to enhance the ummah's quality of life and well-being. This research examines the effects of demographic factors on the development of waqf-based entrepreneurial intention among Muslim students studying in higher educational institutions in Malaysia. Findings from the binary logistic regression analysis of the survey from 400 Muslim undergraduate students in Malaysia show that age and working experience have significant positive impact on the waqf-based intention. The findings of this research will be of interest to the young and educated entrepreneurs and the waqf donators in order to uplift the country's economy. This study focuses only on the demographic factors and hence, future research should add factors which might have potential impact on the intention.